Ø·Ø±Ù‚ Ø§Ù„ØªØ¹Ù„ÙŠÙ… Ø§Ù„ÙØ¹Ø§Ù„ Ù…Ù† Ø®Ù„Ø§Ù„ ÙƒÙØ§ÙŠØ§Øª Ù…Ø¹Ù„Ù…ÙŠ Ù…Ø§Ø¯Ø© Ø§Ù„ØªÙØ³ÙŠØ± - Abdul Rahman, Bunyamin (Al-Banjari : Jurnal Ilmiah Ilmu-Ilmu Keislaman, 2019)
Tafsir is an important subject related to understanding the Qur?an. Therefore, the learning process in this subject should use an effective method, so that the learning process is in accordance with the situation of the students. Researchers have found in textbooks and previous research reports that many of the learning methods used in this field are traditional and modern. The researcher is interested in expressing Tafseer's learning method by considering the responsibility of the interpreter. To achieve this, the researchers examined Tafsir's teaching skills, the extent to which the need to have interpreting skills, and those related to personal, social and professional competencies. By using descriptive-analytic methods, this study found that learning of interpretation depends on three basic things: first, the best method used by teachers during interactive learning because it represents the practical side is the Blended Learning Method; second, learning methods that depend on positive and interactive learning outcomes between teachers and students together such as scientific presentations, dialogues, peer education and cooperative education; and third, ways that train students to take responsibility and respect each other, such as problem-solving, project methods, and programmed education methods that have been widely used in the field of education that are effective and consistent with the requirements of this age.?? ??????? ?? ???? ??????? ?? ?? ???? ?????? ??????? ?????? ???? ????? ??????? ??????? ??? ???? ???? ????? ????? ??????? ?? ?????? ????????. ???? ???? ?? ???????? ?? ???????? ???????? ???????? ??? ??????? ??????? ???? ????? ??????? ??????????? ??? ?????? ????? ??????? ?? ???? ?????? ????????? ????????. ???? ?? ???? ???????? ?? ????? ???????? ???????? ??????? ????? ?? ?????? ?? ??? ??????? ????????? ?? ??? ?????? ?? ??????? ??????? ????? ???????? ??? ??? ??? ????? ??? ??????? ??? ?????? ?????? ????? ???????? ?? ??????? ???? ?? ?????? ??????? ???? ????? ??? ????? ???????. ??????? ??? ??? ???? ???????? ?????? ??????? ?????? ????? ???? ???????? ???? ????? ???? ??????? ??? ??????? ?????? ????? ???? ??????? ???????? ???????? ??????? ??????????? ????????? ?????? ????? ??????? ??? ????? ???? ??????: ????? ????? ???? ???????? ?????? ????? ??????? ???????? ??? ????? ???????? ?? ?????? ?????? ?????? ?????? ??? ???? ?????? ????????? ?????? ??????? ?????? ((Blended Learning Method? ??????? ??? ??????? ???? ????? ?? ???? ????? ???? ?????? ??????? ??? ?????? ??????? ???? ?????? ??? ??????? ???????? ??? ?????? ???????? ????????? ???????? ?????? ??????? ???????? ????????? ??????? ????? ???? ???? ??? ????? ?????? ??? ?????? ????????? ????????? ???????? ???? ????? ??? ????? ?? ????????? ?????? ???????? ?????? ??????? ??????? ???? ??? ????????? ?? ???? ??????? ?????? ???????? ?? ??????? ??? ?????. ??????? ???????? ?? ??? ????? ?????? ?????? ????????.